PRESENÇA DE DUAS ESPÉCIES DE CAIMANINAE (CROCODYLIA, ALLIGATORIDAE) EM MATERIAL OSTEOLÓGICO ORIUNDO DE DESCARTE DA COMUNIDADE AWÁ-GUAJÁ NO ESTADO DO MARANHÃO - Chahud, Artur (Revista Nordestina de Zoologia, 2020)
We analyzed an osteological collection of crocodilians from food disposal deposits of the Guajá Ethnographic Society, located in northwestern of the state of Maranhão. The bone collection represents the accumulation of three years by the Awá-Guajá community in the Indigenous Reserve of Caru. The material is composed by osteoderms, cranial fragments, jaws, and incomplete braincases appendicular bones assigned to subfamily Caimaninae. The objective of this paper is to provide data on the is the identification of the osteological material collected in order to gather data for the interpretation of the processes acting on the osteological material, bone selection and preservation.